PROBLEMS OF BANK CAPITAL ACCESSIBILITY FOR SMALL BUSINESS - Boris B. Bogoutdinov (Plekhanov Russian University of Economics, 2017)
The article discusses issues of interaction between credit managers and entrepreneurs as key components of the crediting process and the speed of access to loan capital for entities of small business. Special attention is paid to enhancing information transparency in relations between state finance institutions and entities of small and medium business. Information openness and positive perception of executive's competence could minimize carelessness risks. On the basis of the research results the authors prove the impact of the moral risk of competent entrepreneurs on the level of 'soft' information transparency aimed at motivating credit managers to make positive decisions.